Intracellular staphylococcus aureus: Live-in and let die - Fraunholz, Martin; Sinha, Bhanu (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus uses a plethora of virulence factors to accommodate a diversity of niches in its human host. Aside from the classical manifestations of S. aureus-induced diseases, the pathogen also invades and survives within mammalian host cells.The survival strategies of the pathogen are as diverse as strains or host cell types used. S. aureus is able to replicate in the phagosome or freely in the cytoplasm of its host cells. It escapes the phagosome of professional and non-professional phagocytes, subverts autophagy, induces cell death mechanisms such as apoptosis and pyronecrosis, and even can induce anti-apoptotic programs in phagocytes. The focus of this review is to present a guide to recent research outlining the variety of intracellular fates of S. aureus.